Sacred Fury: Suggestions Towards an Interpretation of The Faerie Queene - Hartney, Thomas (My University, 1963)
This study of The Faerie Queene has developed from work undertaken at McMaster University in the Session 1962-63. I found a curious lack of balance in the approaches taken by many writers on the poem. There were exceptions, notably Professor Millar Maclure, but the over-all tendency seemed to be neglected the poetry, while bringing an enormous scholarly apparatus to bear on matters which, to me, were of lesser importance.
As the interpretation I sugget and the points upon which I disagree with Spenser scholars are discussed at length in the essay, there is no need to attempt any pith statement of my conclusion here, even if such a statement were possible. I do not pretend to have produced a complete analysis of The Faerie Queene; that would be the work of many lives. What I have attempted is to suggest fruitful directions for reexamination of the poem, to indicate ways in which critical balance may be restored, rather than restore it myself.
I have tried to acknowledge such critical debts as I am aware of, in the course of the essay. Footnote references are inadequate; a critic influences us not only when we quote him, not even only hen we are conscious of his influence. The ideas of a good critic become so much a part of our own consciousness that we present them, in all honesty, as original. I have stood upon the shoulders of giants, and if at times I have failed to acknowledge their assistance, it has not been for want of will. One critical influence, however, is so all-pervading as to demand special thanks. Professor C. S. Lewis has from the beginning conditioned all my thinking about Spenser. Practically the whole essay is, I suspect, to found, in embryonic form, in The Allegory of Love.
Keywords: English Language and Literature; English Language and Literature